Optimalisasi Strategi Pemasaran Usaha Mikro, Kecil dan Menengah.(UMKM) Melalui Pembuatan Logo dan Promosi Berbasis Media Sosial di Kelurahan Tambangan - Rusmewahni, Rusmewahni; Sinaga, Eka Mayastika; Nainggolan, Benhart; Sianaipar, Christin Natalia (Community Service Progress, 2023)
The target of the Real Working Group (KKN) activities entitled "Optimizing the Marketing Strategy for Micro, Small and Medium Enterprises (MSMEs) for Brown Sugar through Logo Creation and Promotion Based on Digital Marketing in Tambangan Subdistrict" is more targeted at the people of Tambangan Subdistrict, in order to increase MSMEs in the Subdistrict. Mining. Several considerations in choosing MSMEs in Tambangan Village have many disadvantages compared to other potential UI'IKM. In this way, we are trying to help maximize sales of MSME products by using a door-to-door system, utilizing social media as a promotional system, and logos on MSME products in Tambangan Village